Total Hemoglobin Mass, Aerobic Capacity, and HBB Gene in Polish Road Cyclists. Issue 12 (December 2016) - Malczewska-Lenczowska, Jadwiga; Orysiak, Joanna; Majorczyk, Edyta; Zdanowicz, Ryszard; Szczepańska, Beata; Starczewski, Michal; Kaczmarski, Jacek; Dybek, Tomasz; Pokrywka, Andrzej; Ahmetov, Ildus I.; Sitkowski, Dariusz
Abstract : Abstract: Malczewska-Lenczowska, J, Orysiak, J, Majorczyk, E, Zdanowicz, R, Szczepańska, B, Starczewski, M, Kaczmarski, J, Dybek, T, Pokrywka, A, Ahmetov, II, and Sitkowski, D. Total hemoglobin mass, aerobic capacity, and the HBB gene in polish road cyclists. J Strength Cond Res 30(12): 3512–3519, 2016—The relationship between genes, amount of hemoglobin, and physical performance are still not clearly defined. The aim of this study was to examine the association between-551C/T and intron 2, +16 C/G polymorphisms in the beta hemoglobin ( HBB ) gene and total hemoglobin mass (tHbmass ) and aerobic capacity in endurance athletes. Total hemoglobin mass and aerobic capacity indices, i.e., V[Combining Dot Above]O2 max, oxygen uptake at anaerobic threshold (V[Combining Dot Above]O2 AT), maximal power output (Pmax), and power at anaerobic threshold (PAT) were determined in 89 young road cyclists, female ( n = 39) and male ( n = 50), who were genotyped for 2 polymorphisms in the HBB gene. The relative values of aerobic capacity indices differed significantly among intron 2, +16 C/G polymorphisms of the HBB gene only in female cyclists; athletes with GG genotype had significantly higher values of V[Combining Dot Above]O2 max ( p = 0.003), V[Combining Dot Above]O2 AT ( p = 0.007), PAT ( p = 0.015), and Pmax ( p = 0.004) than C carriers. No relationships were found between the C-carrier model (CC + CG vs. GG in the case of intron 2, +16 C/G and CC + CT vs. TT for -551 C/T polymorphisms of the HBB gene) and relative values of tHbmass . Our results demonstrated that the HBB gene could be related to aerobic capacity, but it seems that it does not result from an increase in the amount of hemoglobin in the blood.